FERTILITY RATE IN UZBEKISTAN IN THE 20TH CENTURY AGAINST THE BACKGROUND OF SOCIO–DEMOGRAPHIC FACTORS (Konferensiyalar | Conferences, 2024)
The earliest information about the demographic situation of Central Asia, including Uzbekistan, dates to the second half of the 19th century. More accurate statistical data for Uzbekistan became available in the first half of the 20th century because of the 1926 All-Union Population Census.